Paul Samuelson, Robert. V. Roosa, and the economics of credit rationing - Juan C.A. Acosta (Duke University, Center for the History of Political Economy (CHOPE), 2016)
This paper discusses the role played by NY Fed economist Robert Roosa and Paul Samuelson in the emergence of the literature on credit rationing at the beginning of the 1950s. I argue that, contrary to the story one can find in the technical surveys, an intermediate step between Roosa and the models typical of the literature on credit rationing post-1960 took place and was of significant importance in reframing a practitioner's argument into something that could be more easily tackled by economists. Samuelson played a key role in this process and brought out the importance of credit rationing as a phenomenon that should be explained as the outcome of rational agents' behavior.
Keywords: B22; B26; E43; E50; G20; 330; Samuelson; Roosa; credit rationing; banks; monetary policy